Does electronic consent improve the logistics and uptake of HPV vaccination in adolescent girls? A mixed-methods theory informed evaluation of a pilot intervention - Michael Edelstein; Sadie Bell; Sandra Mounier-Jack; Rosie Cooper; Tracey Chantler; Ellen Pringle; Emily Edmundson; Heidi Nielsen; Sheila Roberts (BMJ Open)
Objectives To evaluate the usability and acceptability of an electronic consent pilot intervention for school-based immunisations and assess its impact on consent form returns and human papilloma virus (HPV) vaccine uptake.Design Mixed-methods theory-informed study applying qualitative methods to examine the usability and acceptability of the intervention and quantitative methods to assess its impact.Setting and participants The intervention was piloted in 14 secondary schools in seven London boroughs in 2018. Intervention schools were matched with schools using paper consent based on the proportion of students with English as a second language and students receiving free school meals. Participants included nurses, data managers, school-link staff, parents and adolescents.Interventions An electronic consent portal where parents could record whether they agreed to or declined vaccination, and nurses could access data to help them manage the immunisation programme.Primary and secondary outcome measures Comparison of consent form return rates and HPV vaccine uptake between intervention and matched schools.Results HPV vaccination uptake did not differ between intervention and matched schools, but timely consent form return was significantly lower in intervention schools (73.3% vs 91.6%, p=0.008). The transition to using electronic consent was not straightforward, while schools and staff understood the potential benefits, they found it difficult to adapt to new ways of working which removed some level of control from schools. Reasons for lower consent form return in e-consent schools included difficulties encountered by some parents in accessing and using the intervention. Adolescents highlighted the potential for electronic consent to by-pass their information needs.Conclusions The pilot intervention did not improve consent form return or vaccine uptake due to challenges encountered in transitioning to new working practice. New technologies require embedding before they become incorporated in everyday practice. A re-evaluation once stakeholders are accustomed with electronic consent may be required to understand its impact.